Compliance with Hand Hygiene in Healthcare Facilities: Analysis Based on the Harnos Model and Who Concepts - qizi, Dadayeva Dildora Ikhtiyor; M. I., Bazarbayev (American Journal of Biomedicine and Pharmacy, 2026)
Healthcare-associated infections (HAIs) remain one of the most pressing challenges in modern healthcare systems. The transmission of microorganisms via the hands of medical personnel from one patient to another is considered a leading factor in the spread of these infections. Therefore, strict adherence to hand hygiene is recognized as one of the most effective and cost-efficient measures for infection prevention. Among evidence-based approaches to hand hygiene, the behavior-oriented model developed by Harnos and the “Five Moments for Hand Hygiene” concept proposed by the World Health Organization (WHO) are of particular importance. This study aimed to assess the level of knowledge, attitudes, and practical skills related to hand hygiene among medical students and faculty members involved in medical education.